Obstructive sleep apnea and stroke: The mechanisms, the randomized trials, and the road ahead. (February 2022) - Javaheri, Shahrokh; Peker, Yüksel; Yaggi, H. Klar; Bassetti, Claudio L.A.
Summary: When considered separately from cardiovascular disease, stroke is the third leading cause of death in the U.S. and is the leading cause of long-term disability in adults. New approaches that can be offered to the majority of ischemic stroke patients, can be continued throughout post-stroke care, can limit stroke severity, and can complement or even enhance rehabilitation, would transform ischemic stroke recovery. The treatment of obstructive sleep apnea (OSA) in patients with acute ischemic stroke may represent one such approach. This manuscript reviews the epidemiologic studies of the bidirectional association between OSA and stroke, and the mechanisms and molecular signatures of OSA leading to transient ischemic attack and stroke as well as the randomized controlled trials and observational cohort studies examining continuous positive airway treatment efficacy on the impact of stroke outcomes. Finally, the insights these studies provide on future research are also discussed.